Document Management System Menggunakan Kombinasi Algoritma ROT13 dan Algoritma String Matching - Setiawan, Feri; Fauziah, F (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Technology for document management is really need because it can improve performance both in storage, search and document security. Document management in a manual way can waste time in finding required documents and requiring a lot of space for hardcopy document storage. This study uses a string matching algorithm combined with ROT13 algorithm. String matching algorithm is used to find a file name in database, the file name in database has been encrypted for example plaintext “Kabel Ladder” into chipertext “Xnory Ynqqre”. The steps of string matching algorithm combined with ROT13 algorithm in this study are, word pattern is encrypted and then matched with existing data in database and then a string search in performed using string matching algorithm and produces the data sought. In both algorithm, time and number of matches were tested between pattern and data to show performance of two algorithms using 200 data until 500 data. The result of testing 200 data for search word Tower takes 0.00513 sec and matches 65x, 300 data for search word Tower takes 0.00716 sec and matches 164x, 400 data for search word Tower takes 0.01372 sec and matches 262x and 500 data for search word Tower takes 0.02233 sec and matches 360x. From the test result in this study, the researchers concluded that string matching algorithm combined with ROT13 algoritm, the more data, more time it will take, even though it is still relatively small